An Incentive Mechanism for Building a Secure Blockchain-Based Internet of Things - Ding, Xingjian; Guo, Jianxiong; Li, Deying; Wu, Weili (IEEE transactions on network science and engineering, 2021)
The world-changing blockchain technique provides a novel method to establish a secure, trusted, and decentralized system for solving the security and personal privacy problems in the Internet of Things (IoT) applications. As the mining process in blockchain requires high computational power, the lightweight IoT devices need to purchase computational resources from edge servers and thus can offload their computational tasks. The amount of computational resource purchased by IoT devices depends on how many profits they can get in the mining process, and will directly affect the security of the blockchain network. The security of the blockchain is closely related to the profits of the blockchain platform. Actually, there is a trade-off between blockchain security and the profits of the blockchain platform. In this paper, we investigate the incentive mechanism for the blockchain platform to attract IoT devices to purchase more computational power from edge servers to participate in the mining process, thereby building a secure blockchain network while guaranteeing the profits of the blockchain platform. We model the interaction between the blockchain platform and IoT devices as a two-stage Stackelberg game, where the blockchain platform act as the leader, and IoT devices act as followers. We analyze the existence and uniqueness of the Stackelberg equilibrium, and propose an efficient algorithm to compute the Stackelberg equilibrium point. Furthermore, we evaluate the performance of our algorithm through extensive simulations, and analyze the strategies of the blockchain platform and IoT devices under different situations.